Assessment of hydroxychloroquine maculopathy after cessation of treatment: an optical coherence tomography and multifocal electroretinography study - Moschos MM; Nitoda E; Chatziralli IP; Gatzioufas Z; Koutsandrea C; Kitsos G (Dove Medical Press, 2015)
Marilita M Moschos,1 Eirini Nitoda,1 Irini P Chatziralli,1 Zisis Gatzioufas,2 Chryssanthi Koutsandrea,1 George Kitsos3 1First Department of Ophthalmology, Medical School, National and Kapodistrian University of Athens, Athens, Greece; 2Swiss Eye Research Foundation, Orasis Eye Clinic, Reinach, Switzerland; 3Department of Ophthalmology, Medical School, University of Ioannina, Ioannina, Greece Objective: This study was conducted to evaluate the macular status of patients treated with hydroxychloroquine before and after cessation of treatment.Methods: Forty-two patients with systemic lupus erythematosus underwent ocular examination based on visual acuity evaluation, optical coherence tomography retinal thickness measurements, and multifocal electroretinography (mfERG) records at first visit. The tests were repeated 6 months after treatment withdrawal and compared to the findings at their first visit.Results: Mean visual acuity (measured in log minimum angle of resolution) of both eyes was statistically increased after hydroxychloroquine discontinuation (difference in means: 0.06 [P<0.0001] and 0.01 [P=0.003] for the right and left eyes, respectively). Retinal response amplitudes of central and peripheral areas were significantly improved for both eyes. The following values were observed for central responses: the difference in means was -19.9 (P<0.0001) and -13.6 (P<0.0001) for the right eye and the left eye, respectively; for peripheral responses, difference in means was -10.3 (P<0.0001) and -9.5 (P<0.0001) for right eye and left eye, respectively, after the 6-month examination. There were no statistically significant differences in the retinal thickness of patients after cessation of treatment. The visual acuity of the patients was correlated to central and peripheral mfERG responses (r=-0.53 [P<0.0001] and r=-0.53 [P<0.0001], for the right eye and the left eye, respectively).Conclusion: The visual acuity of patients receiving hydroxychloroquine improves along with the amplitudes of the mfERG responses 6 months after discontinuation of the drug, but no difference in retinal thickness is identified. Keywords: hydroxychloroquine, toxic retinopathy, visual acuity, multifocal electroretinography, optical coherence tomography